TALAQQI: METODE MEMBACA AL QURAN DI PESANTREN NURUL HIKMAH - Rian Nuryana; Nanang Naisabur; Hasan Bisri (STAI AL-FALAH CICALENGKA, 2019)
Today, there are many different types of methods developed in learning the Koran. Everything has advantages and disadvantages. One method that is often done in learning the Koran, namely the method of talaqqi or which is often referred to as the sorogan method. This study aims to determine the effect of the talaqqi method, the ability to read the Koran and the influence of the implementation of the talaqqi method on the ability to recite the Koran in Nurul Hikmah Islamic Boarding School. This research uses inferential descriptive methods. With statistical analysis, the authors process numerical data obtained from 40 respondents, so that it can be known whether or not the influence of the implementation of the talaqqi method on the ability to read the Koran in Nurul Hikmah Islamic Boarding School. The results of this study are as follows: for the X variable (the effect of the talaqqi method) with an average value of this variable equal to 157 with good criteria. Then for variable Y (ability to recite the Koran), the average value of this variable is 155.4 with good criteria. Based on the results of data analysis, it can be concluded that there is an effect of the implementation of the talaqqi method on the ability to read the Koran in the Nurul Hikmah Islamic Boarding School because t_count is greater than t_ (table) (4.1792> 2.0244) with an effect of 31.49%, where the value r = 0.5611 , which gets the